78 Tahun Negara Hukum: Refleksi Atas Upaya Membangun Budaya Hukum Dan Mewujudkan Masyarakat Madani Indonesia - Basuki, Udiyo; Mahya, Amiera Sabiela (Universitas Sang Bumi Ruwa Jurai, 2024)
In its initial period of enactment, the 1945 Constitution emphasized that Indonesia was a legal state. This is stated in several provisions therein, namely Article 27 paragraph (1) and the Explanation of the 1945 Constitution. Entering the reform era which resulted in constitutional amendments, provisions regarding the rule of law are contained in Article 1 paragraph (3) and Article 28D paragraph (1) of the 1945 Constitution The task of the rule of law then is to ensure that law enforcement is achieved. Law enforcement is largely determined by legal culture, because the existence of law is largely determined by legal culture in the form of community values, views and attitudes. Meanwhile, the goal of the state as a mandate for independence, as reflected in the fourth paragraph of the Preamble to the 1945 Constitution, aims at an ideal form of society, namely civil society. Imbued with the spirit of 78 years of independence of the Republic of Indonesia, this article presents efforts to build a legal culture and create a civil society. To achieve these two efforts, several provisions in Law Number 17 of 2007 concerning the 2005-2025 National Long Term Development Plan can be the main reference.